1974 Conference Team - Davidson, Colin; Dubuc, Pierrette; Gamache, Andre; Penner, Rudy; Bertram, Sheila; Dupuis, Onil; Marshall, Eric; Barlow, Beth; Baker, Ray; Alley Heaps, Doreen; Forget, Louis; McPherson, Arlean; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF